Educational regimes in contemporary India - Jeffery, Patricia 1947-; Chopra, Radhika (New Delhi ; Thousand Oaks, CA : Sage Pub., 2005)
"The commonsense understanding of 'education' rests on the assumption that it has a straightforward positive value. However, in practice, education is profoundly ambiguous in its effects. By focusing on 'educational regimes' - and thereby locating values in a broad political terrain encompassing global, national and local contexts - this collection of original essays addresses numerous crucial issues. These include: Whether educational regimes relate to other facets of contemporary Indian society; the extent to which they facilitate the values and ideals enshrined in the Constitution and in policy goals; and the implications of the differential impact of educational regimes on different social groups in India.".
"Combining original research material with new theoretical orientations regarding contexts and ways of learning, this important volume will be welcomed by students and scholars of education, sociology and development studies, as also by teacher training institutes, policy-makers, development agencies and NGOs working in the field of education."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Education -- India; Education and state -- India